Chemical constituents and biological activities of Artocarpus elasticus Reinw ex Blume - Ramli, Faiqah (2013)
Detailed phytochemical investigation has been carried out on leaves and bark of Artocarpus elasticus (Moraceae) collected from two separate locations, Gunung Nuang, Selangor and Sarawak. Various chromatography techniques such as thin layer chromatography (TLC), gravity column chromatographic, vacuum column chromatography, and chromatotron have been used to isolate several compounds of different classes, such as triterpenes, chalcones, flavone, and dihydrobenzoxanthones. Structural elucidations of the pure compounds were carried out using spectroscopic techniques such as UV, IR, NMR, MS and also by comparison with published data. The crude extracts and some isolated compounds were screened for antioxidant activity using 2, 2-diphenyl-1-picrylhydrazyl assay, cytotoxicity by using microculture tetrazolium salt assay and antimicrobial activity using disc diffusion assay. The cell lines used in the cytotoxic assay were human estrogen receptor (ER+) positive breast cancer (MCF-7), human estrogen receptor (ER-) negative (MDA-MB 231), human hepatocarcinoma (HepG2), and normal human cell (WLR-68). For the antimicrobial activity samples were tested against Bacillus ATCC, Bacillus cereus, Bacillus subtilis, Staphylococcus aureus ATCC, Staphylococcus aureus IMR, Staphylococcus pyogenes, Staphylococcus epidermidis, S1211 IMR, Pseudomonas aeruginosa, Klebsiella sp., Pseudomonas multocida, Enterobacter cloacae and Escherichia coli. Isolation work on leaves of Artocapus elasticus collected from Gunung Nuang, Selangor, Malaysia has led to the isolation and identification of three new dihydrochalcones [elastichalcone A (105), elastichalcone B (109), elastichalcone C (107)], cycloartocarpesin (111) along with stigmasterol (96) and p-hydroxybenzoic acid (112). In contrast, detailed study on the bark of Artocarpus elasticus collected from Sarawak afforded one new flavone, elastixanthone (113), together with the known cycloartobiloxanthone (15), artobiloxanthone (79) and artonin E (80). All compounds isolated showed interesting biological activity towards certain bioassays. However, five of the prenylated flavonoids, cycloartobiloxanthone (15), artonin E (80), elastichalcone B (109), cycloartocarpesin (111) dan elastixanthone (113) exhibited good potential for further development as antioxidant agent with IC50 values of 40.02, 11.50, 11.30, 11.89 and 21.60 μg/ml, respectively. Cytotoxic assay carried out on the isolated compound revealed that artonin E (80) possesses potent cytotoxic activity against human estrogen receptor (ER+) positive breast cancer (MCF-7) and human estrogen receptor (ER-) negative (MDA-MB 231) with IC50 value of 2.5 and 15 μg/ml, respectively. Similarly, artonin E (80) and elastichalcone B (109) displayed broad spectrum of antimicrobial activities on the growth of Bacillus ATCC, B. cereus, B. subtilis, S. aureus ATCC, S. aureus IMR, S. pyogenes, E. coli and S. epidermidis.